Secular changes in dementia risk indices among 70-year-olds: a comparison of two Finnish cohorts born 20 years apart - Vire J.; Salminen M.; Viikari P.; Vahlberg T.; Arve S.; Viitanen M.; Viikari L. (Springer International Publishing, 2022)
Aims
To compare dementia risk indices among two separate cohorts of 70-year-olds born 20 year apart.
Methods
Community-dwelling 70-year-old Finns were examined with similar examinations in 1991 (n = 1032) and in 2011 (n = 960). Dementia risk was assessed with the CAIDE Dementia Risk Score (CAIDE) (n = 1516), the Brief Dementia Risk Index (BDRI) (n = 1598) and the Dementia Screening Indicator (DSI) (n = 1462).
Results
The proportion of subjects with moderate or high risk for dementia was significantly higher in earlier than in later born cohort according to CAIDE (99% and 94%, respectively, p < 0.001) and BDRI (41% and 15%, p < 0.001), but not according to DSI (5% and 6%, p = 0.184). The total scores of the earlier born cohort were significantly higher than those of the later born cohort according to all three indices.
Conclusions
According to dementia risk indices, it seems that dementia risk has decreased among community-dwelling 70-year-old subjects during the last decades in Finland.